Cost‐effectiveness analysis of antiviral treatment in the management of seasonal influenza A: point‐of‐care rapid test versus clinical judgment. Issue 2 (29th January 2016) - Nshimyumukiza, Léon; Douville, Xavier; Fournier, Diane; Duplantie, Julie; Daher, Rana K.; Charlebois, Isabelle; Longtin, Jean; Papenburg, Jesse; Guay, Maryse; Boissinot, Maurice; Bergeron, Michel G.; Boudreau, Denis; et al.
Abstract : Background: A point‐of‐care rapid test (POCRT) may help early and targeted use of antiviral drugs for the management of influenza A infection. Objective: (i) To determine whether antiviral treatment based on a POCRT for influenza A is cost‐effective and, (ii) to determine the thresholds of key test parameters (sensitivity, specificity and cost) at which a POCRT based‐strategy appears to be cost effective. Methods: An hybrid « susceptible, infected, recovered (SIR) » compartmental transmission and Markov decision analytic model was used to simulate the cost‐effectiveness of antiviral treatment based on a POCRT for influenza A in the social perspective. Data input parameters used were retrieved from peer‐review published studies and government databases. The outcome considered was the incremental cost per life‐year saved for one seasonal influenza season. Results: In the base‐case analysis, the antiviral treatment based on POCRT saves 2 lives/100 000 person‐years and costs 7600 less than the empirical antiviral treatment based on clinical judgment alone, which demonstrates that the POCRT‐based strategy is dominant. In one and two way‐sensitivity analyses, results were sensitive to the POCRT accuracy and cost, to the vaccination coverage as well as to the prevalence of influenza A. In probabilistic sensitivity analyses, the POCRT strategy is cost‐effective in 66% of cases, for a commonly accepted threshold of 50 000 per life‐year saved. Conclusion: The influenza antiviral treatment based on POCRT could be cost‐effective in specific conditions of performance, price and disease prevalence.